2022
DOI: 10.1101/2022.06.02.494564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controllable membrane damage by tunable peptide aggregation with albumin

Abstract: Aggregation of otherwise soluble proteins into amyloid structures is a hallmark of many disorders, such as Alzheimers and Parkinsons diseases. There is increasing evidence and acceptance that instead of ordered amyloid assemblies, the misfolded oligomer aggregations are the main toxic structures. However, there is no system to study the mechanism and kinetics of aggregation, distinguish between ordered structures and misfolded oligomers, and correlate the structures to their toxicity. The exact role of oligome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Furthermore, we observed that PAIIR can trigger ICD and the release of DAMPs in various cell lines, leading to an enhanced immune response against the influenza vaccination model 18 . Notably, our research also unveiled that using albumin as a modulator can control both peptide aggregation on the cell membrane and their subsequent effects on ICD and DAMP release (Figure 1) 24 .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, we observed that PAIIR can trigger ICD and the release of DAMPs in various cell lines, leading to an enhanced immune response against the influenza vaccination model 18 . Notably, our research also unveiled that using albumin as a modulator can control both peptide aggregation on the cell membrane and their subsequent effects on ICD and DAMP release (Figure 1) 24 .…”
Section: Introductionmentioning
confidence: 66%
“…To induce ICD, we have developed a peptide-aggregation induced immunogenic response (PAIIR) method, which uses engineered peptides made of natural amino acids 19,20 . Inspired by the structures of transmembrane poreforming proteins [21][22][23] , we utilized our molecular framework 19 and designed a pair of oppositely charged peptides [II] that penetrate cells, aggregate, and induce stress and ICD 18,24 . Accumulation of misfolded proteins and their aggregates in the cells cause stress in the endoplasmic reticulum, and depending on the severity of the stress, it may stimulate eukaryote initiation factor 2 alpha (eIF2-) phosphorylation and calreticulin exposure, which are hallmark biomarkers of ICD 25 .…”
Section: Introductionmentioning
confidence: 99%